2012
DOI: 10.1037/a0026836
|View full text |Cite
|
Sign up to set email alerts
|

Social relationships and health: Is feeling positive, negative, or both (ambivalent) about your social ties related to telomeres?

Abstract: Objective The quality of one’s personal relationships has been linked to morbidity and mortality across different diseases. As a result, it is important to examine more integrative mechanisms that might link relationships across diverse physical health outcomes. In this study, we examine associations between relationships and telomeres which predict general disease risk. These questions are pursued in the context of a more comprehensive model of relationships that highlights the importance of jointly consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
146
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 69 publications
6
146
1
1
Order By: Relevance
“…Shorter TL is correlated with negative psychological characteristics, such as pessimism, distress, and hostility (16)(17)(18), although results have not all been consistent (19). By contrast, potentially protective psychosocial factors, such as optimism, social support, and greater educational attainment, have been linked with longer telomeres (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Shorter TL is correlated with negative psychological characteristics, such as pessimism, distress, and hostility (16)(17)(18), although results have not all been consistent (19). By contrast, potentially protective psychosocial factors, such as optimism, social support, and greater educational attainment, have been linked with longer telomeres (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…60 Several studies reported direct associations of engagement in pleasant events with mental and physical health, 61;62 including reduced plasma concentrations of inflammatory biomarkers and lower catecholamine response to stress. 63 …”
Section: Biology Of Positive Psychiatry Constructsmentioning
confidence: 99%
“…While most educational research in this area supports the notion of strong, positive relationships in support of successful reform implementation, recent work also suggests that negative relationships characterized by behavior such as avoidance and gossip may adversely impact such efforts, perhaps even overshadowing the effects of positive ties (Uchino et al 2012). Coupled with the accountability context and negative dispositions toward continuous reforms in education, difficult relationships will likely continue within the landscape of education and may, in fact, increase with additional large-scale change efforts underway (e.g., Common Core state standards).…”
Section: Why So Difficult?mentioning
confidence: 99%
“…This work suggests that maladaptive relationships (e.g., gossip and maltreatment) have negative effects on organizational and relational outcomes (Ellwardt et al 2012;Grosser et al 2010). Moreover, this literature suggests that such negative relationships may, in fact, overshadow the effects of positive ties (Padgett et al 2008;Uchino et al 2012). In this study we examine a particular subset of negative ties, that of "difficult professional relationships," in which actors have difficulty communicating and coming to mutual understanding.…”
Section: Social-network Theory and Negative Tiesmentioning
confidence: 99%
See 1 more Smart Citation